Explicit and Implicit Positive Alcohol Expectancies in Problem and Non-Problem Drinkers: Differences Across Age Groups from Young Adolescence to Adulthood - Vilenne, Aurélie; Quertemont, Etienne (Frontiers in Psychology, 2015)
Aims: Recent studies with animal models showed that the stimulant and sedative effects of alcohol change during the adolescent period. In humans, the stimulant effects of ethanol are most often indirectly recorded through the measurement of explicit and implicit alcohol effect expectancies. However, it is unknown how such implicit and explicit expectancies evolve with age in humans during adolescence. Methods: Adolescent (13-16 year old), young adult (17-18 year old) and adult (35-55 year old) participants were recruited. On the basis of their score on the Alcohol Use Disorder Identification Test (AUDIT), they were classified as non-problem (AUDIT ≤ 7) or problem (AUDIT ≥ 11) drinkers. The participants completed the Alcohol Expectancy Questionnaire (AEQ) and performed two unipolar Implicit Association Test (IAT) to assess implicit associations between alcohol and the concepts of “stimulation” and “sedation”. Results: Problem drinkers from the three age groups reported significantly higher positive alcohol expectancies than non-problem drinkers on all AEQ subscales. Positive alcohol explicit expectancies also gradually decreased with age, with adolescent problem drinkers reporting especially high positive expectancies. This effect was statistically significant for all positive expectancies, with the exception of relaxation expectancies that were only close to statistical significance. In contrast, stimulation and sedation alcohol implicit associations were not significantly different between problem and non-problem drinkers and did not change with age. Conclusions: These results indicate that explicit positive alcohol effect expectancies predict current alcohol consumption levels, especially in adolescents. Positive alcohol expectancies also gradually decrease with age in the three cross-sectional groups of adolescents, young adults and adults. This effect might be related to changes in the physiological response to alcohol.